2016
DOI: 10.1080/15384047.2016.1235663
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti-EPHA2 antibody, DS-8895a for cancer treatment

Abstract: Overexpression of EPHA2 has been observed in multiple cancers and reported to be associated with poor prognosis. Here, we produced an afucosylated humanized anti-EPHA2 monoclonal antibody (mAb), DS-8895a for cancer treatment. The antibody recognizes the extracellular juxtamembrane region of EPHA2 and therefore can bind to both full-length and truncated forms of EPHA2, which are anchored to cell membranes and recently reported to be produced by post-translational cleavage in tumors. DS-8895a exhibited markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…A significant reduction of metastases was observed in the group treated with both ephrinA1-Fc or 135H12 treatments. Therapeutic targeting of the EphA2-LBD has been pursued in recent years by several different approaches [ 6 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and most studies envisioned the use of agonistic agents as vehicles for targeted delivery of chemotherapy [ 17 , 18 , 19 , 20 , 21 , 24 ]. Indeed, we had recently demonstrated that an earlier generation EphA2-targeting-peptide, when conjugated with paclitaxel, was remarkably effective in inhibiting lung metastases in a syngeneic mouse model of breast cancer [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction of metastases was observed in the group treated with both ephrinA1-Fc or 135H12 treatments. Therapeutic targeting of the EphA2-LBD has been pursued in recent years by several different approaches [ 6 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and most studies envisioned the use of agonistic agents as vehicles for targeted delivery of chemotherapy [ 17 , 18 , 19 , 20 , 21 , 24 ]. Indeed, we had recently demonstrated that an earlier generation EphA2-targeting-peptide, when conjugated with paclitaxel, was remarkably effective in inhibiting lung metastases in a syngeneic mouse model of breast cancer [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results were similar to Huang et al [7] and may be explained by that EphA2 stimulates proliferation, migration and spread of GAC cells mainly by increasing the expression of the epithelial mesenchymal transition markers like snail, N-cadherin, b-catenin, stimulating the Wnt/b-catenin pathway and by inhibition of E-cadherin in GAC cells. EPHA2 is overexpressed in a wide range of cancers and is associated with poor prognosis [25]. Many recent studies investigated the RTKs such as EphA2 and reported them as targets for molecular therapy for GAC [26][27][28][29], and also proved that EphA2 overexpression was positively correlated with factors that controlled angiogenesis and invasion in cancer cells because EphA2 receptor activation allowed vascular endothelial growth factor (VEGF)-dependent endothelial cell transport, sprouting, survival and expression of metalloproteinase, and these may be the causes of the poor clinical outcome of cancer patients with EphA2 overexpression, moreover the EphA2-EphrinA1 signaling axis regulates many steps that are essential for carcinogenesis and stimulation of downstream molecules like the phosphatidyl inositol 3' kinases (PI3K), mitogen activated protein kinases (MAPK) and integrins along with epidermal growth factor receptor(EGFR) that regulate cell adhesion, cancer cell growth, metastases and development of vascular network.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that membrane type-1 matrix metalloproteinase (MT1-MMP) on tumor cells cleaves EPHA2 at the extracellular domain and the resultant truncated and membrane-anchoring forms of EPHA2 promote oncogenic signaling [33]. These findings suggest that tumor cells contain truncated forms of EPHA2 on their cell surface which are important for EPHA2-targeting cancer therapy using monoclonal antibodies (mAbs) that mediate antibody-dependent cellular cytotoxicity (ADCC) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, afucosylation of the carbohydrate chain in the Fc domain of another anti-EphA2 mAb (DS-8895a) has been shown to increase the Ab-dependent cellular toxicity (ADCC) and inhibit tumor growth in xenograft mouse models for breast and gastric cancers (Hasegawa et al, 2016). An antagonistic EphB2 Ab, on the other hand, was shown to inhibit the growth of colon carcinoma xenografts only as a conjugate with monomethyl auristatin E, an antimitotic agent (Mao et al, 2004).…”
Section: Targeting the Eph/ephrin Complex For Drug Developmentmentioning
confidence: 99%